2013
DOI: 10.5732/cjc.012.10189
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the survival of patients with nasopharyngeal carcinoma between 1976 and 2005 in Sihui, China: a population-based study

Abstract: Both the incidence and mortality of nasopharyngeal carcinoma (NPC) have decreased in Hong Kong and Taiwan but not in mainland China. The goal of this study was to analyze trends in NPC patient survival between 1976 and 2005 in Sihui, an area of mainland China with a population at high risk for NPC. A total of 1,761 patients diagnosed with NPC between 1976 and 2005 according to the records of Sihui Cancer Registry were followed to the end of 2006. We determined their observed and relative survival rates and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Numerous studies have demonstrated that low hemoglobin (Hb) is a strong prognostic indicator of poor disease control and survival in patients with head and neck squamous cell carcinomas (HNSCC) [1][2][3]. Nasopharyngeal carcinoma (NPC) is a distinct form of HNSCC in terms of epidemiology, pathology, and response to treatment [4][5][6]. Chua and his colleagues reported low mid-radiation Hb levels to be an independent predictor of local disease recurrence in NPC patients [7], which is similar to the findings of previous studies on HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that low hemoglobin (Hb) is a strong prognostic indicator of poor disease control and survival in patients with head and neck squamous cell carcinomas (HNSCC) [1][2][3]. Nasopharyngeal carcinoma (NPC) is a distinct form of HNSCC in terms of epidemiology, pathology, and response to treatment [4][5][6]. Chua and his colleagues reported low mid-radiation Hb levels to be an independent predictor of local disease recurrence in NPC patients [7], which is similar to the findings of previous studies on HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent medical advances have extended the 5-year overall survival rate, there is still no marker for NPC prognosis, except for disease stage (Chen et al, 2014). Unfortunately, the majority of NPC patients in endemic areas are diagnosed at an advanced stage, owing to the relatively inaccessible nasopharynx site and the insidious clinical course of NPC in China (Liu et al, 2013). The development of novel serum biomarkers that could act as a surrogate for clinical examination would allow the detection of NPC at an earlier stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, local relapses and distant metastases frequently occur after radiotherapy alone . Concurrent chemoradiotherapy and the combination with adjuvant chemotherapy significantly prolongs the survival time of NPC patients (Liu et al, 2013). Although recent medical advances have extended the 5-year overall survival rate, there is still no marker for NPC prognosis, except for disease stage (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although nasopharyngeal carcinoma (NPC) is seen in many countries and regions worldwide, it is common in the People’s Republic of China, especially in the south 1. It is reported that approximately 70% of cases are stage III and IV at diagnosis, due to the anatomical structure of the nasopharynx and biological behavior of NPC 2,3.…”
Section: Introductionmentioning
confidence: 99%